Virtual environments for grid computing - Wang, Lizhe (Schriftenreihe des Instituts für Angewandte Informatik - Automatisierungstechnik, Universität Karlsruhe (TH), 2009)
This book therefore proposes a new philosophy of Grid usage: provide virtual computing environments for Grid users. The new methodology could solve the problems currently encountered by Grid computing. It supports desired computing environments for users, which provide customized hardware/software configuration, QoS assurance and manageable functionality. This philosophy also liberates resource providers from the various onerous tasks of resource management.